2022
DOI: 10.1002/1873-3468.14376
|View full text |Cite
|
Sign up to set email alerts
|

Arginyl‐tRNA‐protein transferase 1 (ATE1) promotes melanoma cell growth and migration

Abstract: Arginyl‐tRNA‐protein transferase 1 (ATE1) catalyses N‐terminal protein arginylation, a post‐translational modification implicated in cell migration, invasion and the cellular stress response. Herein, we report that ATE1 is overexpressed in NRAS‐mutant melanomas, while it is downregulated in BRAF‐mutant melanomas. ATE1 expression was higher in metastatic tumours, compared with primary tumours. Consistent with these findings, ATE1 depletion reduced melanoma cell viability, migration and colony formation. Reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…Moreover, protein arginylation has been described as regulating cellular stress response 35,36,37 . Here, we demonstrated that upregulation of ATE1 was associated with UPR response that triggers cell survival in U87MG cells, as previously described in melanoma cells, where increased cell survival was related to ATE1 overexpression under stress condition triggered by serum deprivation 6 . In particular, we observed increased BIP arginylation in U87MG-ATE1+cells (Figure 4)…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Moreover, protein arginylation has been described as regulating cellular stress response 35,36,37 . Here, we demonstrated that upregulation of ATE1 was associated with UPR response that triggers cell survival in U87MG cells, as previously described in melanoma cells, where increased cell survival was related to ATE1 overexpression under stress condition triggered by serum deprivation 6 . In particular, we observed increased BIP arginylation in U87MG-ATE1+cells (Figure 4)…”
Section: Discussionsupporting
confidence: 85%
“…The preliminary in silico analysis of the TCGA-RNASeq dataset for GBM cases 30 and GTEx for normal brain samples 31 demonstrated a differential activation of arginylation between GBM and normal brain samples, and a poorer clinical outcome in GBM cases with increased ATE1 expression. Increased ATE1 level has already been correlated with increased cell migration and metastatic events in melanoma 6 . Although the mechanisms of tumorigenesis related to arginylation are not completely elucidated, arginylation has been linked to cell proliferation through AKT 32 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations